Value of diffusion‐weighted and gadolinium‐enhanced MRI for the diagnosis of pelvic recurrence from colorectal cancer. Issue 2 (31st October 2013) - Colosio, Alban; Soyer, Philippe; Rousset, Pascal; Barbe, Coralie; Nguyen, Francis; Bouché, Olivier; Hoeffel, Christine
<x xml:space="preserve">Abstract</x> Purpose To prospectively assess the added value of gadolinium‐enhanced and diffusion‐weighted (DWI) MRI for the diagnosis of pelvic recurrence from colorectal cancer (CRC). Materials and Methods Fifty‐two patients with suspected pelvic recurrence from CRC underwent pelvic MRI with T2‐weighted ("T2"), gadolinium‐enhanced fat‐suppressed T1‐weighted ("gadolinium") and DWI MR sequences. Three readers (senior radiologist: R1, two residents: R2, R3) scored the likelihood of recurrence on "T2, " "T2 + DWI, " and "T2 + Gadolinium." Results Twenty‐seven patients had 42 sites of pelvic recurrence. On "T2, " R1 achieved AUC of .95, sensitivity 88.4%, specificity 95.2%. For R2, these figures were .89, 81.4%, 90.5%, for R3 .90, 83.7%, 76%. Both Gadolinium injection and DWI significantly improved AUCs for residents but not for the senior radiologist: up to .988 (R2, P = 0.006) and to .98 (R3, P = 0.01) with DWI and to .96 (R2, P = 0.04), .98 (R3, P = 0.01) after gadolinium. All readers achieved slightly better AUCs with "T2 + DWI" than with "T2+Gadolinium" but not significantly (P = 0.68, P = 0.11, P = 0.3; respectively). Conclusion For diagnosis of pelvic recurrence from CRC, both DWI and gadolinium‐enhanced MRI significantly increase diagnostic performances compared with "T2" MRI for residents. DWI may be helpful in patients with contra‐indications to intravenous administration of gadolinium. J. Magn. Reson. Imaging 2014;40:306–313. © 2013 Wiley Periodicals, Inc.